(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
The current research aims to study “The role of anti-self-compulsiveness in creating the mindset of an entrepreneurial leader In the Civil Status Department in Baqubah” And the possibility of successfully applying these two dimensions in the government sector of the city of Baqubah, represented by the Civil Status Department in Baqubah. The research problem came from the main question it is: "Does self-interest have a significant, statistically significant relationship and impact on the mentality of entrepreneurial leaders in the Civil Status Department in Baqubah?" “The existence of a correlation and influence between the roles of self-confidence in creating the mentality of an entrepreneurial leader in the Civil Status Department in Baqubah. On the basis of the research hypotheses and in order to enrich the research with data and information that puts the research at the level of achieving its objectives, these data and information were obtained from references, sources, and periodicals related to the research concepts, On the analytical side, several statistical methods were collected, including: (arithmetic mean, standard deviation, Pearson correlation coefficient, and linear regression) which analyzes the research concepts and its most important dimensions related to the research topic in a way that enables them to be answered accurately. The research population that represents the potential sample was chosen which the Civil Status Department in Baqubah is. The research sample of (90) respondents was selected, it is a deliberate sample where the questionnaire form was distributed to all sample members, The research results were analyzed based on the statistical program (SPSS), which targeted decision-makers in the Civil Status Department in Baqubah, represented by the Office of the General Director, department directors, and division and unit directors. The results of the research reached a set of conclusions, the most important of which was the awareness of the senior leadership in the Civil Status Department in Baqubah of the anti-self-desires in creating the mentality of the entrepreneurial leader. The results of the field analysis also indicated that there is a significant influence on self-confidence in creating the mentality of the entrepreneurial leader.